Analysis of the Implementation of Sharia Compliance on Buddhist Employees in Increasing Sharia Banking Capacity at Islamic Bank - Fathiya Kada-Sae; Fitri Nur Latifah (Universitas Muhammadiyah Sidoarjo, 2023)
Researchers conducted research on sharia compliance with Buddhist employees who work at the Islamic Bank of Thailand, because the Islamic Bank of Thailand is not limited to religion and race for employees. Islamic Bank of Thailand is currently a state company under the supervision of the Ministry of Finance and the Bank of Thailand. Therefore, in this study to find out whether Buddhist employees know and understand about sharia principles in Islamic banks.The research method used is a qualitative research method, with data collection techniques using data from the study of related documents and data from interviews. Research results that can be the result of interviews and related documents. The presentation of the research results is divided into 3 parts as follows: 1. The work factors of Buddhist employees who work in the Islamic bank of Thailand. 2. Islamic Law Regarding Banking Requirements. 3. Services in the Islamic Bank Of Thailand Service Model. From the results of the three research sections, when analyzed together with interviews and related documents, Buddhist employees who work at the Islamic Bank of Thailand adhere to Islamic principles strictly in accordance with the goals of the institution, provide services in accordance with Islamic principles and are impressed by very Islamic user. In the interview, both the Muslim and non-Muslim population commented that they were satisfied with the Islamic Bank of Thailand's convenient services and fulfilled their need to access the service